Novel glomerular filtration markers - George, Jaya A; Gounden, Verena (Advances in clinical chemistry, 2019)
Chronic kidney disease is currently assessed by estimated glomerular filtration rate, a mathematical construct based on creatinine or creatinine and cystatin concentration. Creatinine-based equations have improved with standardization efforts and the Modification of Diet in Renal Disease Study (MDRD) and CKD-Epidemiology Collaboration Study (CKD-EPI). Because the measurement of creatinine is subject to interference from non-GFR determinants, alternative markers have long been sought. These have included cystatin C and low molecular weight proteins like β2-microglobulin and beta trace protein. Tubular disease often occurs before glomerular filtration is impaired and investigators have investigated the excretion of other low molecular weight proteins such as Neutrophil Gelatinase-Associated Lipocalin (NGAL) and Kidney Injury Molecule-1 and N-acetyl-β-d-glucosaminidase. While preliminary, there is some evidence linking these analytes with GFR, disease stage and mortality. Although asymmetrical dimethyl arginine, an inhibitor of nitric oxide, has been shown to be associated with progression of renal disease, symmetric dimethyl arginine may be a better marker. Recent work has also explored the potential of microRNA (miRNA) analysis and metabolomics studies to further elucidate this complex pathophysiologic disease process. Investigators hope to improve our ability to detect CKD by the use of test panels, i.e., various marker combinations thereof. Unfortunately, most of these markers lack standardization unlike traditional measures that rely on creatinine and cystatin C measurement.